On the non-actuality inferences in Turkish avertives - Furkan DİKMEN; Ömer DEMİROK (Dilbilim Araştırmaları Dergisi)
Languages have various forms of expressing implications ofimminency and non-actuality. While a variety of constructions such asimperfectives, proximatives or adverbs like almost crosslinguistically imply thecounterfactuality of the event in question, some languages like French andTurkish have exclusive morphemes expressing imminence while at the sametime logically asserting the non-actuality of an event. This study has a particularfocus on the Turkish morpheme -(y)Ayaz, which when combined with apredicate indicates that the event expressed by the predicate has not beenactualized although it was close to be so. We argue that this is part of what-(y)Ayaz asserts, and provide a compositional semantics for sentences involvingthis morpheme. Finally, we show that our semantics sheds light on thecombinatorial restrictions concerning lexical aspect and outer aspect.